Refleksje nad reformą prawa pracy - Szubert, Wacław (Wydział Prawa i Administracji UAM, 1991)
The reform of the labour law, carried out presently, aims at replacing the syjstem of imperative planning and managing excuted by the State with the democratic legal order based on the idea of respecting the sovereignity of parties to the labour relationship and of their representative organs. However, the chaiiges in the labour law must be in agreement with actual changes in the economic sphere if this branch of law is to maintain its adequacy and efficiency. Besides, attempts should be made to avoid overregulation, especially with respect to collective conflicts (strikes), for the latter are the challenge that can hardly be contained by the use of legal measures.
Some reflection on the reform of the law of work